Recent Advances in Geotechnical Research - Wu, Wei.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a snapshot of the research activities of the Institute of Geotechnical Engineering, University of Natural Resources and Life Sciences in Vienna, Austria. The topics are broad ranged including: · Centrifuge model testing · Constitutive model · Granular physics · Numerical simulation · Soil bioengineering The topics reflect our geotechnical research in a changing world. Traditional topics in foundation engineering are fading out and new topics are emerging. The European Commission is gratefully acknowledged for funding the following projects within its program FP7 and Horizon2020: MUMOLADE (Multiscale modelling of landslide and debris flow), REVENUES (Reinforced Vegetation Numerical Evaluation of Slopes) and GEORAMP (Geohazards - Risk Assessment, Mitigation and Prevention).
From the content: Role of plants - results of pore pressure monitoring in a slope -- A probabilistic 3-D slope stability analysis for forest management -- Effect of eccentricity and boundary on jet formation of soft fine sand -- Experimental and numerical analysis of stick-slip instability of granular materials -- Combination of decisive properties of soil in science and geotechnics -- Effects of mycorrhizal fungi on slope stabilisation functions of plants -- Shear strength of granular soil under saturated and unsaturated conditions -- Failure of unsaturated soil slopes initiated by self-weight loading -- Centrifuge study of soil arching in slope reinforced by piles -- Quantitative description of orthotropic fabric of sand.
Keywords: Engineering geology; Geotechnical engineering; Geoengineering; Geotechnical Engineering and Applied Earth Sciences